Eddy heat flux across the Antarctic Circumpolar Current estimated from sea surface height standard deviation - Foppert, A; Donohue, KA; Watts, DR; Tracey, KL (Journal of Geophysical Research: Oceans, 2017)
Eddy heat flux (EHF) is a predominant mechanism for heat transport across the zonally unbounded mean flow of the Antarctic Circumpolar Current (ACC). Observations of dynamically relevant, divergent, 4 year mean EHF in Drake Passage from the cDrake project, as well as previous studies of atmospheric and oceanic storm tracks, motivates the use of sea surface height (SSH) standard deviation, H*, as a proxy for depth‐integrated, downgradient, time‐mean EHF in the ACC. Statistics from the Southern Ocean State Estimate corroborate this choice and validate throughout the ACC the spatial agreement between H* and EHF seen locally in Drake Passage. Eight regions of elevated EHF are identified from nearly 23.5 years of satellite altimetry data. Elevated cross‐front exchange usually does not span the full latitudinal width of the ACC in each region, implying a hand‐off of heat between ACC fronts and frontal zones as they encounter the different EHF hot spots along their circumpolar path. Integrated along circumpolar streamlines, defined by mean SSH contours, there is a convergence of EHF in the ACC: 1.06 PW enters from the north and 0.02 PW exits to the south. Temporal trends in low‐frequency [EHF] are calculated in a running‐mean sense using H* from overlapping 4 year subsets of SSH. Significant increases in downgradient [EHF] magnitude have occurred since 1993 at Kerguelen Plateau, Southeast Indian Ridge, and the Brazil‐Malvinas Confluence, whereas the other five EHF hot spots have insignificant trends of varying sign.